Dispersión Legítima De Semillas Por Aves En El Bosque Y Matorral Serrano De La Provincia De Córdoba - Dellafiore, Claudia M. (European Scientific Journal, ESJ, 2016)
Birds play a fundamental role in many ecosystems because through endozoochory they can disperse lots of fruits and herefore its seeds. In the southern hemisphere, temperate forests and hills scrub of Córdoba-Argentina are characterized by great floristic diversity and an important richness of birds. However, only few studies focusing on the role of birds as dispersers of fruits and seeds have been conducted in this ecosystem. The aims of this study was to investigate if birds are dispersing fruits or seeds in the forest and hills scrub; analyse if fruits or seeds dispersion is scattered along seasons; and to assess whether seeds suffer physical damage when passing through the digestive tract of birds. During July, August, September and December 2012, fruits and seeds from birds pellets were collected while walking through two linear transects (length and width) of 1,450 x 20 and 1,200 x 5 m, respectively. Results showed that birds dispersed seeds during all seasons although the largest proportion was observed during autumn and winter when more than 70% of birds pellets contained seeds. The highest proportion of damaged seeds occurred in September (11%), but overall proportion of seeds that had physical damage was very low. Finally, our results revealed that birds have an important role in seeds dispersion on the forest and hills scrub ecosystem, and most of these dispersed seeds were exotic.